Recombinant Salmonella enterica serovar Typhimurium vaccine vector expressing green fluorescent protein as a model antigen or human immunodeficiency virus type 1 subtype C Gag - Chin'ombe, Nyasha (Division of Virology, 2014)
Includes bibliographical references (leaves 172-200).